Analysis Misconceptions Middle School Students in Padang Barat on Temperature, Heat and Expansion Material Use Instrument Four Tier Test - Siti Maryam; Khairil Arif; Azza Nuzullah Putri; Rani Oktavia; Nellisma; Deni Angraini (Postgraduate, University of Mataram, 2024)
The aim of this research is to determine the profile of junior high school students' misconceptions regarding temperature, heat and expansion in Padang Barat sub-district. The method used in this research is the quantitative descriptive method Four Tier Test. This research involved 80 class VII junior high school students in Padang Barat District. The results of the research are students' misunderstanding of the concepts of temperature, heat and expansion in Padang Barat District Middle School (68%) which is relatively high. Based on data analysis, it is known that students have the highest misconception regarding the concept of explaining temperature (81%).